He-Ar isotopic signatures of the Mesozoic granitoids in South Korea: implications for genesis of the granitic magma and crustal evolution in NE continental margin of the Eurasian plate - Kim, Kyu Han; Nagao, Keisuke; Sumino, Hirochika; Lee, Jong Ik; Park, Jisun (Geosciences journal (Seoul, Korea), 2024)
In order to constrain the granitic magma source at the northeastern continental margin of the Eurasian plate, noble gas isotopic ratios such as helium ( 3 He/ 4 He), argon ( 40 Ar/ 36 Ar) and neon ( 20 Ne/ 22 Ne, 21 Ne/ 22 Ne) were determined for Mesozoic quartz and biotite minerals from granitic rocks in the Korean peninsula. 3 He/ 4 He ratios in fluid inclusions of quartz samples have a wide range from 0.005 to 0.522 R A (av. 0.095 R A ) and 0.013 to 1.27 R A (av. 0.37 R A ) (R A =1.40 × 10 −6 , atmospheric value) for Jurassic (Daebo) and Cretaceous (Bulguksa) granites, respectively. The 3 He/ 4 He ratios clearly show a contribution of mantle-derived He to the granitic rock at the formation, then the helium has been deeply affected by accumulation of in situ produced radiogenic 4 He and/or crustal helium. Although these ratios are lower than those of the subcontinental lithospheric mantle (SCLM) (6.1 ± 0.9 R A ), mantle helium has been traced in these Mesozoic I-type granites from South Korea. The observations imply that the helium of SCLM source predominates over all of the Jurassic granites in South Korea and the Cretaceous granites in the Ogcheon belt (OB), and suggests that the granitic magma was derived from the partial melting product of SCLM materials with appreciable amounts of radiogenic helium. Meanwhile, Cretaceous granites were originated from igneous mantle source materials beneath the Gyeongsang basin, south-eastern area of the Korean peninsula. A presence of mantle components ( 20 Ne/ 22 Ne ≈ 10.13) and/or nucleogenic Ne were identified in some quartz and most biotite samples of granitoids in Jurassic age. Argon isotopic ratios (av. 40 Ar/ 36 Ar = 2370) of fluid inclusions in quartz for Jurassic granites are considerably higher than those in Cretaceous granites (av. 40 Ar/ 36 Ar = 414), indicating a clear aging effect. He-Ar isotopic signatures together with the characteristics of Nd, Sr, and O isotopes can lead to the conclusion that the generation of Jurassic granitic magma was responsible for the subduction of the Izanagi oceanic plate. Meanwhile, the subduction ridge (e.g., the Kula-Pacific Ridge) model is likely to be a suitable scenario for formation of the Cretaceous granitic magma in the Korean peninsula.